Answer:
c
ccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccccc
First we use product rule
y=x^2lnx
dy/dx = x^2 d/dx (lnx) + lnx d/dx (x^2)
dy/dx = x^2 (1/x) + lnx (2x)
dy/dx = x + 2xlnx
now taking second derivative:
d2y/dx2 = 1 + 2[x (1/x) + lnx (1)]
d2y/dx2 = 1 + 2[1+lnx]
1+2+2lnx
3+2lnx is the answer
Answer:I think it's -23.72
Step-by-step explanation:Step 1: Reduce the fraction
Step 2: Multiply
Step 3: Calculate
step 4: solution
Answer:
idk try to figure it pouy
Step-by-step explanation: